2014
DOI: 10.1371/journal.pone.0100310
|View full text |Cite
|
Sign up to set email alerts
|

Key Role of the Endothelial TGF-β/ALK1/Endoglin Signaling Pathway in Humans and Rodents Pulmonary Hypertension

Abstract: Mutations affecting transforming growth factor-beta (TGF-β) superfamily receptors, activin receptor-like kinase (ALK)-1, and endoglin (ENG) occur in patients with pulmonary arterial hypertension (PAH). To determine whether the TGF-β/ALK1/ENG pathway was involved in PAH, we investigated pulmonary TGF-β, ALK1, ALK5, and ENG expressions in human lung tissue and cultured pulmonary-artery smooth-muscle-cells (PA-SMCs) and pulmonary endothelial cells (PECs) from 14 patients with idiopathic PAH (iPAH) and 15 controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
87
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(91 citation statements)
references
References 32 publications
(50 reference statements)
2
87
1
1
Order By: Relevance
“…We have data suggesting that INHBB expression is positively correlated with that of ALK1 and TGF‐βR2 (unpublished data, 2009). In endothelial cells, TGF‐β activated ALK1, which transmits signals through the ALK1/Smad1/5 pathways and, to a lesser degree, the Smad2/3 signaling pathways, stimulated endothelial cell proliferation and migration . Thus, we have reason to believe that INHBB can induce the anoikis‐resistant cell EMT modification through the TGF‐β/Smads pathway to affect tumor growth, invasion, and metastasis (Figure ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have data suggesting that INHBB expression is positively correlated with that of ALK1 and TGF‐βR2 (unpublished data, 2009). In endothelial cells, TGF‐β activated ALK1, which transmits signals through the ALK1/Smad1/5 pathways and, to a lesser degree, the Smad2/3 signaling pathways, stimulated endothelial cell proliferation and migration . Thus, we have reason to believe that INHBB can induce the anoikis‐resistant cell EMT modification through the TGF‐β/Smads pathway to affect tumor growth, invasion, and metastasis (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…pathways and, to a lesser degree, the Smad2/3 signaling pathways, stimulated endothelial cell proliferation and migration. [43][44][45] Thus, we have reason to believe that INHBB can induce the anoikis-resistant cell EMT modification through the TGF-β/Smads pathway to affect tumor growth, invasion, and metastasis ( Figure 6).…”
mentioning
confidence: 99%
“…TGF-β has been reported to contribute to PAH development, as endothelial TGF-β/activin receptor-like kinase 1/endoglin signaling leads to pulmonary blood vessel angiogenesis, macrophage infiltration, and cytokine expression in the lungs (23,24). The present study identified miR-148-3p in PAH, and identified TGF-β as a potential target of miR-148-3p.…”
Section: Discussionmentioning
confidence: 99%
“…While PAH can be induced by the overexpression of IL‐6 and TNFα, BMP signaling inhibits the TNFα‐induced activation of NF‐κB by promoting an MRTF‐A/NF‐κB inhibitory complex, thereby preventing inflammation in PASMCs [Wang et al, ]. Interestingly, mutations in members of the TGFβ superfamily of receptors, such as endoglin and the activin‐like receptor 1 (ALK‐1), have also been observed in PAH [Gore et al, ]. Therefore, further investigation remains necessary to determine whether TGFβ‐induced miR‐142‐3p plays an anti‐inflammatory role in VSMCs by targeting pro‐inflammatory cytokines such as IL‐6.…”
Section: Discussionmentioning
confidence: 99%